Analysis of the Negotiation Period of the XXI Collective Working Agreement of PT Freeport Indonesia on the Rights of Workers - Annisa Aprilia Purba (Budapest International Research and Critics University, 2022)
Disputes are a reality that cannot be separated from human life, not least in the Collective Labor Agreement (PKB) negotiation forum. The existence of negotiations is one of the determining processes in the decline, stagnation, or increase in workers' rights, of course, followed by the rights and obligations of each in a balanced manner. The results of this study indicate that the disputes that occurred in the PT Freeport Indonesia Collective Labor Agreement negotiations were a form of realistic disputes in the form of interests with the demands, benefits, strengths, resources, and values to be achieved by both parties through the proposals of the parties. which is fought for acceptance becomes a provision in the collective labor agreement. The workers are trying to improve the fulfillment of workers' rights, while the employers are of the opinion that the obligations and rights of each party have been fulfilled in a balanced way. However, the absence of restrictions on collective bargaining agreements will have implications for the period of implementation of the fulfillment of the rights of workers stipulated in the new collective labor agreement and will have an impact on the collective work agreement of the company or contractor who is a joint partner of PT Freeport Indonesia.